Acts of conscience : Christian nonviolence and modern American democracy - Kosek, Joseph Kip (Columbia studies in contemporary American history., 2009)
In response to the massive bloodshed that defined the twentieth century, American religious radicals developed a modern form of nonviolent protest, one that combined Christian principles with new uses of mass media. Greatly influenced by the ideas of Mohandas Gandhi, these ""acts of conscience"" included sit-ins, boycotts, labor strikes, and conscientious objection to war. Beginning with World War I and ending with the ascendance of Martin Luther King Jr., Joseph Kip Kosek traces the impact of A.J. Muste, Richard Gregg, and other radical Christian pacifists on American democrati.